Gift of gold - Krentz, Jayne Ann (Thorndike, Me. : Five Star, 1997)
From Jayne Ann Krentz, award-winning author of A Coral Kiss and the bestselling Midnight Jewels, comes an intriguing contemporary romance in which a beautiful young woman becomes ensnared in a web of desire and vengeance.
70979
Keywords: Man-woman relationships -- Fiction. -- Colorado; Women cooks -- Fiction. -- Colorado; Colorado -- Fiction; Romantic suspense novels